Effects of planting density and the composition of wheat cultivar mixtures on stripe rust: an analysis taking into account limits to the replication of controls - Mundt, C. C.; Garrett, Karen A. (My University, 2011)
The effect of plant density on disease is not well understood in populations of a single host plant genotype and has been studied even less in mixtures of host genotypes. We performed an experiment to evaluate the effect of wheat planting density on infection by Puccinia striiformis in experimental plots with a single wheat genotype and in plots with two genotypes making up a range of frequencies. Stripe rust severity in single-genotype plots increased with planting density in 1997 but decreased with planting density in 1998. Disease in host mixtures was compared to the weighted mean of disease levels in the corresponding single-genotype plots. The design of the field experiment included limited replication of these reference treatments (that is, there was not a unique pair of single-genotype plots for each mixture plot); therefore, we devised an analysis based on collapsing the data into independent mean observations. Disease reduction due to host diversity was less when one genotype predominated than when both host genotypes were present at nearly equal frequencies. The greatest mean host-diversity effect for reduced disease was at the intermediate planting density of 250 seeds per m2.
Keywords: Planting density; Wheat cultivar mixtures; Stripe rust; Cultivar mixtures; Mixture analysis; Mixture models; Triticum aestivum